(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Polymerase chain reaction (PCR) is a molecular biology method that allows amplification of specific DNA fragments. PCR has found wide application in disease diagnostics, forensic medicine, as well as in genomics and biotechnology research. This technique has provided scientists with a powerful tool for analyzing genetic information, opening up new horizons in science and medicine.